Analysis of hydrological variability over the Volta river basin using in-situ data and satellite observations - Awange, J.L. (2020)
By combining satellite altimetry with Gravity Recovery and Climate Experiment derived terrestrial water storage-TWS (2002–2014), this study used a two-step procedure based on spherical harmonic synthesis and statistical decomposition to support the understanding of the Volta basin's natural hydrology and its freshwater systems. Results indicate that Lake Volta contributed 41.6% to the observed increase in TWS over the basin during the 2002–2014 period. While it also coincides with observed decline in net precipitation (−15 mm/yr), the long dry periods in the basin (2001–2007) also contributed to this storage depletion. The Lake Volta shows sensitivity to incoming flows of the Volta river system with a lag spanning between less than one and up to two years. In addition to this, a 4–5 year cycle in the clustering of dry and wet periods resulting from the impact of climate variability on the basin was noticed.